Test Fluid Products

JP3250189UActive Publication Date: 2025-02-17ASAKUSA TABLET LAB CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024003854U
Authority / Receiving Office
JP · JP
Patent Type
Utility models
Current Assignee / Owner
Priority Date
2020-05-18
Filing Date
2024-11-20
Publication Date
2025-02-17
Estimated Expiration
2031-05-12

Smart Images

  • Figure 0003250189000001_ABST
    Figure 0003250189000001_ABST
Patent Text Reader

Abstract

To provide a test liquid product in which a test liquid to be used for an elution test is degassed beforehand and then filled in an airtight container. Also to provide a test liquid product using a container in which elution of organic solvent components, antioxidant components, etc. is suppressed. [Solution] This test liquid product 1 is filled with a test liquid 2 that has been degassed in advance, so that the tester does not have to take the trouble of performing a complicated degassing operation. In addition, the container body 3 suitable for this test liquid product 1 has a sealant film of the laminated film that constitutes the container body 3 made of additive-free polyolefin, and at least the sealant film to the barrier film are laminated directly or via a solvent-free adhesive layer that does not contain organic solvents, without using any adhesive or anchor coating agent that contains organic solvents. Therefore, components such as organic solvents do not elute into the contents, and adverse effects of these eluted substances on the contents can be prevented.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a test liquid product containing a test liquid used for dissolution testing or disintegration testing of solid preparations. [Background technology]

[0002] In solid pharmaceutical preparations for oral administration, such as tablets, capsules, and granules, even if the active ingredient is the same in amount, the dissolution rate of the active ingredient after administration may cause a difference in clinical efficacy. For this reason, dissolution testing is positioned as one of the important quality control items in pharmaceutical manufacturing, and is one of the tests prescribed based on the harmonization agreement of the Japanese Pharmacopoeia, the United States Pharmacopoeia, and the European Pharmacopoeia. For example, the 17th revised Japanese Pharmacopoeia (17th Bureau) stipulates that "This test is performed to determine whether oral preparations comply with the dissolution test specifications, but also aims to prevent significant bioequivalence," and specifies in detail the equipment to be used, the operation method, the judgment method, etc. In addition, it is required to confirm that the dimensions of the dissolution test equipment are within the specified tolerances, and to regularly check important parameters that need to be monitored during the test, such as the temperature of the test liquid, the volume of the test liquid, and the rotation speed of the paddle and basket. Regarding the test liquid, the volume of the test liquid must be within ±1% of the specified volume, the temperature of the test liquid must be maintained within 37°C ±0.5°C, and if the test liquid is a buffer solution, the pH must be adjusted to within ±0.05 of the specified value.

[0003] The test fluids used are a first dissolution test fluid with a pH of 1.2, a second dissolution test fluid with a pH of 6.8, water, and various buffer solutions. For example, in the production of solid preparations, in quality control, tests are simultaneously performed on at least six samples from each batch using the type of test fluid, the amount of test fluid, and the test conditions determined for each preparation, to determine whether the preparation complies with the dissolution test standard.

[0004] Conventionally, the test solution for dissolution tests was prepared by the tester on demand based on the Japanese Pharmacopoeia, or a fixed amount was prepared and used, but this was a heavy burden for the tester. For example, when performing a dissolution test using the rotating basket method or the paddle method, the tester must weigh and dissolve and mix the reagents and water before starting the test, adjust the pH, and prepare the necessary test solution (at least six times the amount of the test solution specified for one test in order to test at least six samples. Usually, 900 mL is used for one test, so 900 mL x 6, or 5,400 mL of test solution, is required), and then accurately measure (within ±1%) the specified amount of test solution from that, place it in a specified container, and heat it to the specified temperature (usually 37°C) before the test can begin. This means that a great deal of time and effort is required before the test can begin.

[0005] Since the test liquid is basically prepared under atmospheric conditions by the tester, air that is in equilibrium with the room temperature at the time of preparation is dissolved in the test liquid. It is known that the solubility of gas generally decreases as the temperature increases. Therefore, when the test liquid is heated to the test temperature of 37°C, the air that was dissolved in the test liquid at the time of preparation gradually volatilizes into the atmosphere. However, since this volatilization rate is slow, even at 37°C, supersaturated air still remains in the test liquid, and after the start of the test, this may generate bubbles during the test and adversely affect the dissolution results.

[0006] Here, the 17th Revised Japanese Pharmacopoeia clearly states as a precaution that "Gases dissolved in the test liquid may cause bubbles and affect the test results. If dissolved gases affect the results of the dissolution test, degas the liquid before the test" and provides examples of degassing methods. For example, the 17th Revised Japanese Pharmacopoeia specifies that "The test liquid is heated to 41°C while being stirred, and immediately filtered through a filter with a pore size of 0.45 μm or less while being stirred under suction, and then stirred for 5 minutes under reduced pressure. Other validated degassing methods may also be used." This degassing method is also a time-consuming operation that requires heating the test liquid and filtration under reduced pressure.

[0007] Therefore, when performing a dissolution test on a preparation for which the use of a degassed test liquid is specified as described above, a degassing operation is required to degas the test liquid to be used to a specified degree of degassing immediately before the start of the test. The degassed test liquid is then immediately transferred into a test container, and the test is started only after it is quickly heated to the specified temperature of 37°C. In addition, various devices have been marketed as in Non-Patent Documents 1 and 2 to reduce the burden of the degassing operation, but they require the burden of purchasing the device and maintaining the device, as well as the need to prepare a separate test liquid as described above, the effort required to transfer the prepared test liquid to the device, and the work of dividing the degassed test liquid from the degassing device into smaller portions, and are therefore insufficient to reduce the burden on testers.

[0008] On the other hand, test solutions prepared in advance should be stored in containers with retractable lids that allow for small portions to be taken out, in a manner that prevents water evaporation, changes in pH, and the growth of microorganisms. In addition, when preparing degassed test solutions for storage, they should be stored in airtight containers that do not reabsorb air, and the degassed state required for testing should be maintained.

[0009] In the development and manufacture of solid dosage forms, disintegration tests are also conducted to confirm whether the dosage form disintegrates in a test solution within a specified time. Although the test solution used in this disintegration test does not necessarily require degassing, other procedures are similar to those for dissolution tests, which places a heavy burden on the tester.

[0010] Thus, in order to carry out a dissolution test or disintegration test, a great deal of time and effort is required from the tester before the start of the test, and the effort increases even more when degassing is required.

[0011] However, as shown in Non-Patent Documents 3 and 4, for example, products in which the test liquids used in dissolution tests or disintegration tests are filled in containers or their concentrates are now available on the market. These products tend to reduce the burden on test executors compared to when the test liquids are prepared by the test executors themselves, as the test liquids can be used as is or the concentrates can be diluted with water.

[0012] The container shapes for these test liquids are generally hard PE bottles, reduced volume polyethylene containers, Kewpie containers, etc., and the container sizes available on the market are 3 L to 20 L when the internal liquid is the test liquid, and 3 L to 10 L when the internal liquid is a concentrated liquid. In addition, the following [Patent Document 1] discloses an invention relating to a test liquid product in which a container is filled with a test liquid used for dissolution testing or disintegration testing of solid preparations.

[0013] The container used for the test liquid product described in [Patent Document 1] is composed of a laminated film including a metal oxide vapor deposition film and a sealant film arranged as the innermost layer, and when laminating the metal oxide vapor deposition film and the sealant film, an adhesive is used to increase the interlayer peel strength between the metal oxide vapor deposition film and the sealant film. The adhesive used is a compound such as an isocyanate compound, polyethyleneimine, modified polybutadiene, or an organic titanate compound dissolved in an organic solvent such as methanol or ethyl acetate. In addition, an antioxidant such as butylhydroxyanisole (BHA) or dibutylhydroxytoluene (BHT) is usually added to the polyolefin film used as the sealant film. BHA and BHT are compounds that have been used for many years as pharmaceutical additives and food additives, and are considered to be highly safe for the human body. [Prior art documents] [Patent documents]

[0014] [Patent Document 1] JP 2014-70964 A [Non-Patent Document 1] "De-stress injection device 'EMD-21P'", [online], Higuchi Shokai Co., Ltd., [searched on August 27, 2020], Internet <URL:https: / / www.higuchi-inc.co.jp / business-products / pharmaceuticals / analysis / [Non-Patent Document 2] "Dissolution test liquid heating and degassing tank HDR-250" [online], Toyama Sangyo Co., Ltd., [Retrieved August 27, 2020], Internet <URL: https: / / www.toyamas.co.jp / products / dissolution / [Non-Patent Document 3] "Reagents for pharmaceutical stability testing", [online], Kanto Chemical Co., Ltd., [searched March 16, 2020], Internet <URL:https: / / products.kanto.co.jp / web / index.cgi?c=t_product_table&pk=413&_ga=2.259041225.210980883.1584262288-1651687052.1582866595> [Non-Patent Document 4] "Disintegration and dissolution test reagents", [online], Fujifilm Wako Pure Chemical Industries, Ltd., [searched March 16, 2020], Internet <URL:https: / / labchem-wako.fujifilm.com / jp / category / 00636.html Summary of the Invention [Problem to be solved by the invention]

[0015] Here, these test liquid products, including the invention described in [Patent Document 1], are simply prepared test liquids or their concentrated solutions filled in containers and sealed, and are not degassed. Therefore, when conducting a dissolution test that requires degassing, the tester must degas these test liquids immediately before starting the test.

[0016] Dissolution tests are tests to measure the rate at which active ingredients dissolve from pharmaceutical preparations into a dissolution test medium, and typically, ultraviolet absorption measurement methods or high performance liquid chromatography (HPLC) methods are used to quantify the amount of active ingredients in the test medium. In the HPLC method, an ultraviolet absorbance detector is often used as a detector. Therefore, it is desirable for the dissolution test medium to have no ultraviolet absorption.

[0017] However, for example, in the case of the test liquid product described in Patent Document 1, when the laminated film constituting the container uses an adhesive or anchor coating agent containing an organic solvent when laminating the metal oxide vapor deposition film and the sealant film, or when the sealant film contains an antioxidant such as BHA or BHT, the solvent components of the adhesive or anchor coating agent or the antioxidant components of the sealant film may dissolve into the test liquid, and the ultraviolet absorption of these solvent components and antioxidant components may have a negative effect on the dissolution test.

[0018] The present invention has been made in consideration of the above circumstances, and aims to provide a test liquid product in which the test liquid to be used in the elution test is degassed beforehand and then filled into an airtight container, and also aims to provide a test liquid product in which the elution of organic solvent components, antioxidant components, etc. is suppressed. [Means for solving the problem]

[0019] The present invention is (1) The above problem is solved by providing a test liquid product 1 having a test liquid 2 used in dissolution testing or disintegration testing of solid preparations and a container body 3 filled with the test liquid 2, characterized in that the amount of dissolved air in the test liquid 2 is 0 mg / L to 6 mg / L in terms of dissolved oxygen concentration. (2) When the dissolved oxygen concentration of the test liquid 2 is x and the volume ratio of the head space 30 in the container body 3 to the amount of the test liquid 2 is y, y≦-0.0231x 3 +0.1867x 2 -0.6804x+2.3516 The above-mentioned problems are solved by providing the test liquid product 1 described in (1) above, which is characterized by satisfying the above. (3) The above problem is solved by providing the test liquid product 1 described in (2) above, which is characterized in that the dissolved oxygen concentration of the test liquid 2 is 0 mg / L to 4.5 mg / L, and the volume ratio of the head space 30 in the container body 3 to the amount of the test liquid 2 is 0 vol% to 1 vol%. (4) The above problem is solved by providing a test liquid product 1 described in any one of (1) to (3) above, characterized in that the filling amount of the test liquid 2 is within the range of ±1% of the specified volume for one dissolution test. (5) The above problem is solved by providing a test liquid product 1 described in any one of (1) to (4) above, characterized in that the container body 3 includes a sealant film 111 made of additive-free polyolefin, and a barrier film 113 having inorganic barrier layers 113b, 113c on one or both sides of a base film 113a made of a thermoplastic resin, and is composed of laminate films 101A to 101C in which the sealant film 111 and the barrier film 113 are directly laminated together. (6) The above problem is solved by providing a test liquid product 1 described in any one of (1) to (4) above, characterized in that the container body 3 includes, in this order, a sealant film 111 made of additive-free polyolefin, a plastic film 112 made of thermoplastic resin, and a barrier film 113 having inorganic barrier layers 113b, 113c on one or both sides of a base film 113a made of thermoplastic resin, and is composed of laminate films 301A to 301C in which the sealant film 111 and the plastic film 112 are directly laminated together, and the plastic film 112 and the barrier film 113 are directly laminated together. (7) The above problem is solved by providing a test liquid product 1 described in any one of (1) to (4) above, characterized in that the container body 3 includes a sealant film 111 made of additive-free polyolefin and a barrier film 113 having inorganic barrier layers 113b, 113c on one or both sides of a base film 113a made of a thermoplastic resin, and the sealant film 111 and the barrier film 113 are bonded together by a solventless adhesive layer that does not contain an organic solvent, thereby forming a laminated film 101A to 101C. (8) The above problem is solved by providing a test liquid product 1 described in any one of (1) to (4) above, characterized in that the container body 3 comprises, in this order, a sealant film 111 made of additive-free polyolefin, a plastic film 112 made of thermoplastic resin, and a barrier film 113 having inorganic barrier layers 113b, 113c on one or both sides of a base film 113a made of thermoplastic resin, and the sealant film 111 and the plastic film 112 are bonded together by a solventless adhesive layer that does not contain an organic solvent, and the plastic film 112 and the barrier film 113 are bonded together by a solventless adhesive layer that does not contain an organic solvent, thereby forming a laminated film 301A to 301C. (9) The above problem is solved by providing a test liquid product 1 described in any one of (5) to (8) above, characterized in that the container body 3 is composed of laminate films 201A to 201C, 401A to 401C further having a cover film 114 made of a thermoplastic resin on the barrier film 113 side. Effect of the Invention

[0020] The test liquid product according to the present invention is filled with a degassed test liquid, so that it is possible to omit some or all of the preparatory work for the elution test, including the degassing work. This significantly reduces the workload of the tester. In addition, the container of the test liquid product according to the present invention suppresses the elution of organic solvent components and antioxidant components, and prevents the adverse effects of these components on the contents. As a result, the test liquid product according to the present invention can obtain more accurate test results. [Brief description of the drawings]

[0021] [Figure 1] 1 is a cross-sectional view of a first embodiment of a laminated film used in a container of a test liquid product according to the present invention. [Diagram 2] 1 is a cross-sectional view of a second embodiment of a laminated film used in a container of a test liquid product according to the present invention. [Diagram 3]1 is a cross-sectional view of a third embodiment of a laminated film used in a container of a test liquid product according to the present invention. [Figure 4] 1 is a cross-sectional view of a fourth embodiment of a laminated film used in a container of a test liquid product according to the present invention. [Diagram 5] 1 is a perspective view showing one embodiment of a test liquid product according to the present invention; [Figure 6] 1 is a perspective view showing one embodiment of a test liquid product according to the present invention; [Figure 7] 1 is a graph showing the relationship between the dissolved oxygen concentration and the head space volume ratio of a test liquid. [Figure 8] 1 is a graph plotting the head space volume ratio at which each sample provides an upper limit of the degree of degassing. [Figure 9] 1 is a flow chart showing an example of a method for producing a test liquid product according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] An embodiment of the test liquid product according to the present invention will be described with reference to the drawings. First, a container suitable for the test liquid product 1 according to the present invention will be described. The container of the test liquid product 1 shown here is suitable for the present invention, but is not necessarily limited thereto, and well-known containers such as metal containers, glass containers, various plastic containers, and plastic film bags other than those described below can be used. First, a schematic perspective view of the test liquid product 1 using a container suitable for the present invention is shown in Figs. 5 and 6. The container suitable for the test liquid product 1 according to the present invention includes a bag-shaped container body 3 for accommodating the contents, and the container body 3 is composed of laminated films 101A to 401C shown in Figs. 1 to 4. The test liquid product 1 according to the present invention is filled with the above-mentioned container and test liquid 2 used for dissolution test or disintegration test of solid preparations.

[0023] Here, the test liquid 2 of the test liquid product 1 according to the present invention is, as described above, a dissolution test liquid or a disintegration test liquid, and is not particularly limited, and may be one described in the Japanese Pharmacopoeia, the United States Pharmacopoeia, the European Pharmacopoeia, etc., or one prepared by a unique method in accordance with the Pharmacopoeia. Specific dissolution test liquids include buffer solutions of various pH values ​​from pH 1.2 to 8.0, and water (purified water). Examples of the buffer solutions include the first dissolution test liquid (pH 1.2), acetic acid / sodium acetate buffer solution (pH 4.0), the second dissolution test liquid (pH 6.8), phosphate buffer solution (pH 6.8), and phosphate buffer solution (pH 8.0) described in the 17th Revised Japanese Pharmacopoeia. For example, in the disintegration test method described in the 17th Revised Japanese Pharmacopoeia, three types of disintegration test liquids are used: the first disintegration test liquid (pH 1.2), the second disintegration test liquid (pH 6.8), and water. The first disintegration test liquid and the first disintegration test liquid are the same. Therefore, the test liquid product 1 filled with water or the first liquid for the dissolution test as the test liquid 2 can also be used as the test liquid product 1 for the disintegration test.

[0024] In addition, if the gas dissolved in the test liquid 2 affects the results of the dissolution test, it is necessary to degas the test liquid before the test. The test liquid 2 of the test liquid product 1 according to the present invention is degassed to a predetermined degree of degassing in advance. Here, the example of the degassing method of the test liquid 2 in the 17th revised Japanese Pharmacopoeia states, as mentioned above, that "the test liquid is heated to 41°C while stirring, immediately filtered through a filter with a pore size of 0.45 μm or less while stirring under suction, and further stirred under reduced pressure for 5 minutes. Other validated degassing methods may be used." Meanwhile, the "Dissolution Test Toolkit" published by the United States Pharmacopoeia (USP) in the United States for the industrial world states that the USP degassing standard is to heat an appropriate amount of test liquid to 41°C to 45°C, filter through a 0.45 μm membrane filter at a reduced pressure of 100 mbar or less, and stir under reduced pressure for another 5 minutes. In addition, it is described as a precaution that the degassed test liquid will reabsorb air more quickly if it is stirred vigorously or roughly handled, and that the degassed test liquid should be used immediately. In addition, other degassing methods may be used, but they must be equivalent to the USP degassing method, and the specific degree of degassing must be measured using a dissolved gas meter and must not exceed 6 ppm in dissolved oxygen concentration.

[0025] For these reasons, the degassing degree of the degassed test liquid 2 is required to be 6 ppm (6 mg / L) or less in terms of dissolved oxygen concentration. Therefore, in the test liquid product 1 according to the present invention, the amount of dissolved air in the test liquid 2 after filling is set to 0 mg / L to 6 mg / L in terms of dissolved oxygen concentration. There is no particular limitation on the method of degassing the test liquid 2, and in addition to the above-mentioned method described in the Japanese Pharmacopoeia or the method described in the United States Pharmacopoeia (USP), well-known degassing methods such as the use of various commercially available degassing devices for testing and research, industrial degassing devices, heat degassing method, reduced pressure degassing method, ultrasonic degassing method, degassing method using a hollow fiber membrane, and helium replacement can be used alone or in combination. And, according to the test liquid product 1 according to the present invention, the tester can immediately use the test liquid 2 for a dissolution test or disintegration test without degassing it.

[0026] As described above, the test liquid 2 degassed to a dissolved oxygen concentration of 6 mg / L or less is filled into a known container or the container body 3 shown in Figures 5 and 6 to obtain a test liquid product 1. Ideally, the container is completely filled with the test liquid 2, and it is most desirable to fill the container without forming a so-called head space 30 so that no excess air (residual air 5) remains, and then immediately seal the container. This is because if the known container or the container body 3 shown in Figures 5 and 6 is sealed while the residual air 5 remains in the head space 30, the residual air 5 may redissolve in the test liquid 2 and the degree of degassing may decrease. The effect of the residual air 5 on the degree of degassing of the test liquid 2 depends on the amount of the residual air 5 and the relative proportion of the degassed test liquid 2. Therefore, the amount of the residual air 5, i.e., the volume of the head space 30, when the degassed test liquid 2 is filled into the container must be strictly controlled.

[0027] For this reason, the inventor carried out the following experiment on the effect of the amount of residual air 5 on the degassing degree. First, purified water as the test liquid 2 was degassed by a known method to prepare test liquids 2 with dissolved oxygen concentrations of 2.9 mg / L, 4.5 mg / L, 5.1 mg / L, 5.3 mg / L, 5.4 mg / L, and 6.1 mg / L, respectively. Next, 900 mL of test liquid 2 (purified water) with each dissolved oxygen concentration was placed in a standing pouch bag of aluminum laminate (laminated film 101B described below with aluminum foil as the second inorganic barrier layer 113c) with a capacity of 1 L as the container body 3, and the remaining air 5 was removed using a degassing sealer to fill the pouch to capacity, and then the pouch was sealed. Next, an injection syringe was inserted into the container body 3, and 0.0 mL (no injection), 2.5 mL, 5.0 mL, and 10.0 mL of air was injected into the test liquid 2 with each dissolved oxygen concentration to form the remaining air 5, and a head space 30 was formed. Immediately afterwards, the injection hole was sealed with aluminum tape. Next, these samples were left at room temperature for 10 days, and then opened to measure the dissolved oxygen concentration of test liquid 2. Here, the relationship between the dissolved oxygen concentration of test liquid 2 after being left for 10 days and the head space volume ratio (volume of head space 30 / volume of test liquid) is shown in Figure 7.

[0028] 7, it can be seen that the dissolved oxygen concentration after aging for 10 days increases as the volume of the head space 30, i.e., the amount of remaining air 5, increases. This is thought to be because the remaining air 5 dissolves in the test liquid 2 over time.

[0029] Next, from the data in Fig. 7, the volume ratio of the headspace 30 at which each sample after aging had an upper limit of 6 mg / L in degassing was calculated using an approximation formula, and the results of plotting these values ​​are shown in Fig. 8. Here, the horizontal axis of Fig. 8 indicates the initial (at the time of filling) dissolved oxygen concentration of the test liquid, and the vertical axis indicates the headspace volume ratio. When the initial dissolved oxygen concentration of the test liquid 2 is x and the headspace volume ratio is y, the approximation curve (dashed line in Fig. 8) of the plot in Fig. 8 showing the allowable value of the headspace volume ratio is given by the following formula (1). y=-0.0231x 3 +0.1867x 2 -0.6804x+2.3516··(1) The region below the approximation curve in FIG. 8 (the curve showing the allowable headspace value), i.e., the region expressed by the following formula (2), means the region in which the dissolved oxygen concentration does not exceed 6 mg / L, which is the specified deaeration degree, even if the remaining air 5 in the headspace 30 is dissolved in the test liquid 2. y≦-0.0231x 3 +0.1867x 2 -0.6804x+2.3516··(2) Therefore, in the test liquid product 1 of the present invention, the dissolved oxygen concentration x of the test liquid 2 and the volume ratio y of the head space 30 in the container body 3 satisfy equation (2) (located in the area below the approximation curve in Figure 8).

[0030] The degree of degassing of the test liquid 2 sufficiently degassed by a known degassing method generally indicates a dissolved oxygen concentration of 4.5 mg / L or less. Here, the allowable headspace value y when the dissolved oxygen concentration is 4.5 mg / L is 0.97% ≒ 1% ​​according to the above formula (1). Therefore, the test liquid 2 that has been subjected to a normal degassing operation satisfies the above formula (2) by making the headspace 30 1% or less of the volume of the test liquid 2, that is, 0 vol% to 1 vol%. Therefore, even if the headspace 30 is formed in a container of the test liquid 2 that has been subjected to a normal degassing operation, if the volume of this headspace 30 is 1 vol% or less, the test liquid 2 can maintain a dissolved oxygen concentration of 6 mg / L or less even after time has passed. This simplifies the criteria for the quality of the headspace 30 in the test liquid product 1.

[0031] The capacity of the known container or container body 3 is not particularly limited as long as it is within a range capable of accommodating a predetermined amount of the test liquid 2, but considering the effect of reducing the burden on the tester and ease of transportation, it is preferably within the range of (filling amount of the test liquid 2 + 30 mL) to (filling amount of the test liquid 2 + 300 mL), and particularly preferably within the range of (filling amount of the test liquid 2 + 50 mL) to (filling amount of the test liquid 2 + 150 mL). For example, when 900 mL of the test liquid 2 is filled, it is preferably 930 to 1200 mL, and more preferably 950 to 1050 mL. If the capacity of the known container or container body 3 is the filling amount of the test liquid 2 + 30 mL or more, the test liquid 2 is unlikely to leak when the container is opened, and if the capacity is the filling amount of the test liquid 2 + 300 mL or less, the container does not become excessively large when a predetermined amount of the test liquid 2 is filled, and the amount of waste after use is small.

[0032] The filling amount of test liquid 2 is preferably within the range of [n times the volume specified as the amount of test liquid used in one run of a dissolution test or disintegration test] ±1% (where n is an integer from 1 to 6), and particularly preferably within the range of the volume specified as the amount of test liquid used in one run of a dissolution test or disintegration test ±1%.

[0033] When n is 1, that is, when the filling amount of the test liquid 2 is within ±1% of the volume used in one dissolution test or disintegration test, the tester can start the dissolution test or disintegration test by simply opening the well-known container or container body 3 and transferring the content liquid (test liquid 2) directly to the test container. When n is 2 to 6, such as 2700 mL for three tests (n=3) or 5400 mL for six tests (N=6), the test liquid product 1 needs to be accurately divided into portions of a specified test liquid volume (e.g., 900 mL). However, if the filling amount is within 6 times the specified test liquid volume, the test liquid product 1 is sufficiently light (e.g., in the case of a dissolution test, the specified test liquid volume is a maximum of 900 mL, so the mass of the test liquid product 1 itself is a maximum of about 5400 mL), making it easy to transport, divide the test liquid 2, and so on. Furthermore, if the volume is within 6 times, the volume of the test liquid product 1 is sufficiently small, and it is easy to preheat the test liquid product 1 in a container in a thermostatic bath or the like to 37°C. Furthermore, if the volume is within 6 times, the test liquid 2 can be used up quickly after opening the container, and microbial contamination and proliferation after opening are unlikely to occur. In particular, in the dissolution test, at least 6 samples are tested under the same conditions, so the entire amount can be used up at one time.

[0034] The amount of test liquid used in one dissolution test is specified for each formulation in the Japanese Pharmacopoeia, etc., but is usually 900 mL. Therefore, when the test liquid 2 is a dissolution test liquid, the filling amount of the test liquid 2 is preferably within the range of (900 mL x 1 to 6) ± 1% from the viewpoint of versatility, and is particularly preferably within the range of 900 mL ± 1%. However, there are cases where the test liquid amount is not 900 mL (for example, 500 mL), and it is not limited to the above range. The filling amount can be set according to the amount of each specified test liquid.

[0035] In addition, the amount of test liquid used in one disintegration test is, for example, specified in the disintegration test method described in the 17th revised Japanese Pharmacopoeia, "The amount of test liquid to be put in the beaker should be such that when the test vessel rises to its highest point, the screen surface of the test vessel is at least 15 mm below the liquid surface, and when the test vessel falls to its lowest point, the screen surface should be 25 mm or more from the bottom of the beaker, and the test vessel should not be completely submerged." There is no clear specification for the amount of liquid. Therefore, the amount of test liquid to be used in one disintegration test is specified by the tester so as to satisfy the above-mentioned regulations in accordance with the device used for the disintegration test, and is generally around 900 mL. Therefore, even when the test liquid 2 is a disintegration test liquid, the filling amount of the test liquid 2 is preferably within the range of (900 mL ± 1%) × 1 to 6, and particularly preferably within the range of 900 mL ± 1%.

[0036] Here, the container body 3 of the test liquid product 1 according to the present invention shown in Fig. 5 is a so-called side gusset type gusset bag, and has a spout (mouth member) 4 attached liquid-tightly to the upper part of the container body 3. The container body 3 shown in Fig. 5 is configured with a first film 11 and a second film 12, a first gusset film 13 provided between one side edge of the first film 11 and one side edge of the second film 12, and a second gusset film 14 provided between the other side edge of the first film 11 and the other side edge of the second film 12. The first gusset film 13 and the second gusset film 14 are each bent toward the inside of the container body 3. Then, one side edge of the first film 11 is heat-sealed to one side edge of the first gusset film 13, the other side edge of the first gusset film 13 is heat-sealed to one side edge of the second film 12, the other side edge of the second film 12 is heat-sealed to one side edge of the second gusset film 14, and the other side edge of the second gusset film 14 is heat-sealed to the other side edge of the first film 11, forming four side edge seal parts. Also, the inner faces of the first film 11, the second film 12, the first gusset film 13, and the second gusset film 14 are heat-sealed to each other at the upper part to form an upper seal part 16. Also, the inner faces of the first film 11, the second film 12, the first gusset film 13, and the second gusset film 14 are heat-sealed to each other at the lower part to form a lower seal part.

[0037] In the upper seal section 16, it is preferable that the contact surfaces of the first gusset film 13 and the contact surfaces of the second gusset film 14 are sealed to each other. The sealing of the contact surfaces of the first gusset film 13 and the second gusset film 14 in the upper seal section 16 is performed, for example, by forming punch holes (not shown) at opposing positions near the side edges of the first gusset film 13 and the second gusset film 14, and heat sealing the inner surface of the first film 11 and the inner surface of the second film 12 within the punch holes. In addition, the contact surfaces of the first gusset film 13 and the contact surfaces of the second gusset film 14 in the upper seal section 16 may be directly bonded to each other by heat sealing using an adhesive or a film having heat sealing properties, or by double-sided adhesive tape.

[0038] The first film 11, the second film 12, the first gusset film 13, and the second gusset film 14 are respectively constituted by laminate films 101A to 101C, 201A to 201C, 301A to 301C, and 401A to 401C, which will be described later.

[0039] The spout 4 has an injection tube 21 that is inserted into the container body 3 and that injects the content (test liquid 2), and a cap 22 that is screwed onto the upper part of the injection tube 21 to seal the outlet of the injection tube 21. The spout 4 is attached liquid-tight to the upper seal part 16 by heat sealing, with the injection tube 21 being sandwiched between the upper edges of the first film 11 and the second film 12. When the cap 22 is attached, the container body 3 is in a sealed state. When the cap 22 is removed, the injection tube 21 communicates between the inside and outside of the container body 3. The test liquid product 1 shown in FIG. 5 is provided with the spout 4 with the cap 22, so that it is easy to open and seal, and the content (test liquid 2) can be easily poured into a glass vessel for dissolution testing, etc., which is useful for shortening the preparation time for testing. It is preferable to adopt a tamper-evident plug structure for the spout 4, which leaves evidence of opening once the spout 4 has been opened. Once the test liquid product 1 has been opened, the pH of the contained test liquid is likely to change. Therefore, by adopting a tamper-evident plug structure, it is possible to check whether the test liquid product 1 has been opened, and the quality of the test liquid 2 can be guaranteed.

[0040] The material of the spout 4 is a synthetic resin, at least in the portion sealed with the inner surface of the first film 11 and the second film 12 of the injection tube 21. Examples of the synthetic resin forming at least the sealed portion of the injection tube 21 of the spout 4 include polyolefin resin, polyamide resin, polyester resin, (meth)acrylic resin, vinyl chloride resin, vinylidene chloride resin, polyethersulfone, and ethylene-vinyl alcohol copolymer. Among them, polyolefin resin is preferable because of its excellent processability and low cost. Examples of the polyolefin resin include polyethylene-based resins such as high-density polyethylene, medium-density polyethylene, high-pressure low-density polyethylene, linear low-density polyethylene, and ethylene-vinyl acetate copolymer; olefin-based elastomers such as ethylene-α-olefin copolymer; polypropylene-based resins such as polypropylene, ethylene-propylene random copolymer, and α-olefin-propylene random copolymer; and cyclic polyolefin resins. These resins may be blended to improve performance, or may be partially crosslinked to improve heat resistance. Furthermore, spout 4 may be formed from a single material, or may have a multi-layer structure made up of various resin layers. However, from the viewpoint of sealing performance, it is preferable that the resin forming at least the sealing portion of injection tube 21 of spout 4 is formed from the same type of resin as the resin forming the innermost layer of first film 11 and the innermost layer of second film 12.

[0041] The container body 3 of the test liquid product 1 according to the present invention shown in FIG. 6 is a standing pouch having a body 3a made of a pair of films and a bottom 3b made of a film. The pair of films constituting the body 3a are welded at the side edges and upper edges to form side edge seals 4a, 4b and upper edge seal 4c. The film constituting the bottom 3b is folded in half and placed between the pair of films constituting the body 3a with the half-folded fold line facing up, and one side and the other side of the film constituting the bottom 3b with the fold line as a boundary are welded to the lower edge of the opposing film of the pair of films constituting the body 3a, respectively, to form lower edge seals 4d, 4e. In the area where the side edge seals 4a, 4b and the lower edge seals 4d, 4e overlap, the pair of films constituting the body 3a are partially welded to each other. Furthermore, notches 5a, 5b are provided in the side edge seal portions 4a, 4b slightly below the lower end of the upper edge seal portion 4c, respectively, in order to facilitate opening of the container body 3. And, laminate films 101A-101C, 201A-201C, 301A-301C, 401A-401C, which will be described later, are used as the pair of films constituting the body portion 3a and the film constituting the bottom portion 3b.

[0042] The layer structures of the laminate films 101A to 401C forming the container body 3 may be the same or different, but it is preferable to use laminate films 101A to 401C that all include a sealant film 111 made of the same type of resin, since this makes it easier to heat seal the laminate films 101A to 401C together.

[0043] The container body 3 of the test liquid product 1 according to the present invention is not limited to the form shown in FIG. 5 and FIG. 6 as described above. For example, it may be a gusset bag having a different shape from the container body 3 shown in FIG. 5, or a bag other than the gusset bag. It may also be a standing pouch having a different shape from the container body 3 shown in FIG. 6, or a bag other than the standing pouch. It may also be a well-known container such as a bottle made of metal, glass, or various plastics. However, in terms of the effect of improving the work efficiency, it is preferable that the container is self-supporting, and it is more preferable that it is a gusset bag or a standing pouch like the container body 3 in FIG. 5 and FIG. 6. Examples of the container body 3 other than the gusset bag or the standing pouch include flat bags such as a three-sided sealed bag, a four-sided sealed bag, and a bag with a cut edge for easy opening (for example, a three-sided sealed bag with a notch). The container body 3 may be only a bag-shaped container body 3 composed of the laminated films 101A to 401C, or a container with a spout. However, a bag-shaped container body 3 equipped with a spout 4 is preferred from the standpoint of ease of taking out the test liquid 2 and minimizing waste after taking out the test liquid 2. In this configuration, the container body 3 is equipped with a spout 4 with a cap 22, which makes it easy to open and seal, and also makes it easy to pour the test liquid 2 into a glass vessel for dissolution testing or the like, further shortening the preparation time for the test.

[0044] Next, an example of a manufacturing method of the test liquid product 1 according to the present invention shown in Figs. 5 and 6 will be described with reference to the flow chart in Fig. 9. First, materials such as purified water, inorganic salts, and hydrochloric acid for manufacturing the test liquid 2 are prepared (raw material acquisition step S102). Next, these materials are weighed and charged into a preparation tank made of PE (polyethylene), PP (polypropylene), SUS316L, or the like having chemical resistance, and the target test liquid 2 is prepared according to the regulations of the Japanese Pharmacopoeia, for example, by stirring and dissolving (test liquid preparation step S104). Next, the test liquid 2 is degassed (degassing step S106). For this degassing, various well-known degassing devices for testing and research, industrial degassing devices, degassing modules, etc. can be used. Then, the test liquid 2 is degassed to a degree of degassing with a dissolved oxygen concentration of 4.5 mg / L or less by this degassing step S106.

[0045] In parallel with this, a container body 3 is prepared using the laminated films 101A to 401C (container obtaining step S108). The container body 3 to be filled with the test liquid 2 may be a commercially available product as long as it uses the laminated films 101A to 401C, or may be produced using the laminated films 101A to 401C. The method for producing the container and container body 3 is not particularly limited, and can be carried out by a known method.

[0046] Then, a preset amount of the test liquid 2 of ±1% (for example, 900 mL ±1%) is filled into the container body 3 using a known liquid filling device such as a tube pump or a syringe pump (filling step S110). Next, if the container body 3 has a spout 4, the remaining air 5 in the container body 3 is removed using a known sealing member such as a vacuum capper, and the spout 4 with the cap 22 is fixed to seal the container body 3. If the container body 3 does not have a spout 4, the remaining air 5 in the container body 3 is removed using a known sealing member such as a vacuum sealer, and the opening of the container body 3 is sealed to seal the container body 3. At this time, the volume of the remaining air 5 in the container body 3, i.e., the head space 30, is set to 1% or less of the volume of the test liquid 2 (sealing step S112). Furthermore, since the dissolved oxygen concentration of the test liquid 2 is 4.5 mg / L or less, by making the volume of the head space 30 1% or less of the capacity of the test liquid 2, even if the remaining air 5 in the head space 30 dissolves in the test liquid 2, the dissolved oxygen concentration of the test liquid 2 will not exceed the specified value of 6.0 mg / L.

[0047] Next, if necessary, the product after the sealing step S112 may be sterilized (sterilization step S113). This sterilization can be performed, for example, under conditions of moist heat sterilization at 120°C for 30 to 60 minutes. Next, a label indicating the contents is attached to the surface of the container body 3 (labeling step S114), and the test liquid product 1 according to the present invention is completed.

[0048] Next, the laminated film used in the test liquid product 1 according to the present invention will be described. Here, "(meth)acrylic acid" is a general term for acrylic acid and methacrylic acid. In addition, a numerical range expressed using "~" includes the numerical values ​​on both sides of "~" in the numerical range.

[0049] [Laminated film] First embodiment <<Basic form of the first embodiment>> A first embodiment of the laminated film of the present invention will be described with reference to Fig. 1A. In order to distinguish it from the modified examples described later, the embodiment shown in Fig. 1A may be particularly referred to as the "basic form".

[0050] The laminated film 101A of this embodiment includes a sealant film 111 and a barrier film 113. This basic barrier film 113 has a first inorganic barrier layer 113b on the side of the base film 113a opposite to the side facing the sealant film 111. In the laminated film 101A of this embodiment, the sealant film 111 and the barrier film 113 are laminated directly or via a solventless adhesive layer that does not contain an organic solvent. In other words, neither an adhesive containing an organic solvent nor an anchor coating agent is present between the sealant film 111 and the barrier film 113.

[0051] (Sealant Film 111) The sealant film 111 of this embodiment is a layer that imparts heat sealability to the laminated film 101A, and melts when the laminated film 101A is heat-sealed to form a bag (the shape of the container body 3), and bonds the laminated film 101A to other films that are in contact with the sealant film 111. The sealant film 111 is made of additive-free polyolefin to which no antioxidant, lubricant, antiblocking agent, etc. are added. When the test liquid product 1 is constructed using the laminated film 101A of this embodiment, the sealant film 111 comes into contact with the test liquid 2, which is the content. Here, since conventional (not additive-free) sealant films contain antioxidants such as BHA (butyl hydroxyanisole) or BHT (dibutyl hydroxytoluene) that have ultraviolet light absorption, these ultraviolet light absorbing components may dissolve into the test liquid 2, adversely affecting the results of the dissolution test and disintegration test. However, in the laminated film 101A of this embodiment, since the sealant film 111 made of additive-free polyolefin is used, the ultraviolet absorbing component does not dissolve into the test liquid 2.

[0052] Furthermore, additive-free polyolefins are characterized by not dissolving ultraviolet absorbing components into the test liquid 2, and by having heat sealability and being less likely to be adsorbed by the test liquid 2. Examples of additive-free polyolefins include additive-free polyethylenes such as additive-free high density polyethylene (additive-free HDPE), additive-free low density polyethylene (additive-free LDPE), and additive-free linear low density polyethylene (additive-free LLDPE), additive-free polypropylene, and additive-free polybutene. Among these, additive-free polyethylene is preferred because it can be heat sealed at low temperatures, and additive-free LLDPE is particularly preferred because it has high strength.

[0053] The thickness of the sealant film 111 is not particularly limited, but is usually about 20 to 300 μm. The sealant film 111 may be made of a single sheet of additive-free polyolefin film, or may be made by laminating two or more sheets of additive-free polyolefin films directly or via a solvent-free adhesive layer that does not contain an organic solvent. In this case, neither an adhesive containing an organic solvent nor an anchor coating agent is contained between the additive-free polyolefin films.

[0054] (Barrier Film 113) The barrier film 113 is a film with excellent gas barrier properties such as water vapor barrier properties, and the laminated film 101A of the present embodiment including the barrier film 113 also has excellent gas barrier properties. By filling the container body 3 made of the laminated film 101A with the test liquid 2, evaporation of water from the test liquid 2 during storage of the test liquid product 1 is suppressed, and the test liquid product 1 can be stably stored for a long period of time without reducing the amount of the test liquid 2. In addition, when the test liquid 2 is degassed, re-dissolution of air from the outside of the container body 3 into the test liquid 2 can be suppressed, and a decrease in the degree of degassing can be suppressed.

[0055] The base film 113a is made of a thermoplastic resin. From the viewpoints of film strength, puncture strength, transparency, etc., examples of the thermoplastic resin used for the base film 113a include polyester resins such as polyethylene terephthalate (PET) and polyethylene-2,6-naphthalate (PEN), and polyamide resins such as nylon 6, nylon 66, nylon 12, and copolymer nylon. In addition, the base film 113a is preferably an unstretched or stretched film made of these thermoplastic resins. In particular, polyester resins are preferable because they have excellent dimensional stability and are less likely to crack in the vapor deposition film. In addition, if a thermoplastic resin without antioxidants, lubricants, antiblocking agents, etc. is used for the base film 113a, ultraviolet absorbing components will not be eluted into the test liquid 2. In addition, the base film 113a may be made of one sheet of additive-free thermoplastic resin film, or may be made by laminating two or more sheets of additive-free thermoplastic resin films directly or through a solvent-free adhesive layer that does not contain organic solvents. In this case, neither an adhesive containing an organic solvent nor an anchor coating agent is present between the films of additive-free thermoplastic resin.

[0056] The first inorganic barrier layer 113b is preferably a metal foil, a metal vapor deposition film, or an inorganic oxide vapor deposition film. The metal foil is preferably a foil of at least one metal selected from the group consisting of aluminum, chromium, zinc, gold, silver, platinum, and nickel, and is more preferably an aluminum foil. The metal may be one or more kinds. The thickness of the metal foil is preferably 5 to 200 μm, and more preferably 15 to 20 μm. When the thickness of the metal foil is within the above range, the laminate film 101A has good barrier properties and good flexibility.

[0057] The metal vapor deposition film is preferably a vapor deposition film of at least one metal selected from the group consisting of aluminum, chromium, zinc, gold, silver, platinum, and nickel, and more preferably an aluminum vapor deposition film. The metal may be one or more. The thickness of the metal vapor deposition film is preferably 5 to 300 nm, more preferably 10 to 100 nm. The thickness of the metal vapor deposition film is measured by a quartz crystal type film thickness monitor or a spectrophotometer. When the thickness of the metal vapor deposition film is within the above range, the laminated film 101A has good barrier properties and good flexibility. The metal vapor deposition film can be formed by vapor depositing a metal on the surface of the base film 113a by, for example, a vacuum deposition method, a sputtering method, a chemical vapor deposition method, an ion plating method, or the like.

[0058] The inorganic oxide vapor deposition film is preferably a vapor deposition film of at least one inorganic oxide selected from the group consisting of metal oxides, fluorides, sulfides, and nitrides. Examples of the metal oxide include Al2O3 (aluminum oxide, alumina), SnO2 (tin oxide), CeO2 (cerium oxide), Ta2O5 (tantalum pentoxide), Cr2O3 (chromium oxide), Ti3O5 (titanium pentoxide), Ga2O3 (gallium oxide), TiO (titanium monoxide), Fe2O3 (iron oxide), TiO2 (titanium dioxide-titania), HfO2 (hafnium oxide, hafnia), WO3 (tungsten oxide), and the like. Examples of the inorganic oxide include tin oxide, ITO (In2O3+SnO2), Y2O3 (yttrium oxide, yttria), MgO (magnesium oxide, magnesia), Yb2O3 (ytterbium oxide), Nb2O5 (niobium pentoxide), ZnO (zinc oxide), NiO (nickel oxide), ZrO2 (zirconium oxide-zirconia), SiO (silicon monoxide), ZRT2 (ZrO2+TiO2), and SiO2 (silicon oxide). Among these, silicon oxide, aluminum oxide, or magnesium oxide is preferred, and silicon oxide or aluminum oxide is more preferred, in view of the high transparency of the vapor-deposited film and ease of availability. The inorganic oxide may be one type or two or more types. The thickness of the vapor-deposited film of the inorganic oxide is preferably 5 to 300 nm, and more preferably 10 to 100 nm. The thickness of the vapor-deposited film of the inorganic oxide is measured using a quartz crystal resonator type film thickness monitor or a spectrophotometer. The inorganic oxide vapor deposition film can be formed by vapor depositing an inorganic oxide on the surface of the base film 113a by a method such as vacuum deposition, sputtering, chemical vapor deposition, or ion plating.

[0059] The thickness of the barrier film 113 is preferably 5 to 500 μm, more preferably 7 to 200 μm, from the viewpoints of mechanical strength, flexibility, and transparency. The barrier film 113 has a water vapor permeability of 1.0 g / m or less, measured by the Mocon method under conditions of 40° C. and a relative humidity of 90% RH. 2 / day or less, and 0.5 g / m 2 / day or less is more preferable. The barrier film 113 may be one manufactured by a known manufacturing method, or a commercially available product. For example, a commercially available silicon oxide vapor deposition film is a transparent vapor deposition high gas barrier film (Techbarrier (registered trademark), manufactured by Mitsubishi Chemical Corporation).

[0060] First Modification of the First Embodiment A first modified example of the first embodiment of the laminate film of the present invention will be described with reference to Fig. 1B. The laminate film 101B of the first modified example includes a sealant film 111 and a barrier film 113. The barrier film 113 of the first modified example has a second inorganic barrier layer 113c on the surface of the base film 113a facing the sealant film 111.

[0061] (Sealant Film 111) It is similar to the basic sealant film 111 described above. (Barrier Film 113) The barrier film 113 is a film with excellent gas barrier properties such as water vapor barrier properties, and the laminated film 101A of the present embodiment including the barrier film 113 also has excellent gas barrier properties. By filling the bag made of the laminated film 101A with the test liquid 2, evaporation of water from the test liquid 2 during storage of the test liquid product 1 is suppressed, and the test liquid product 1 can be stably stored for a long period of time without a decrease in the amount of the test liquid 2.

[0062] The base film 113a is made of a thermoplastic resin. From the viewpoints of film strength, puncture strength, transparency, etc., examples of the thermoplastic resin used for the base film 113a include polyester resins such as polyethylene terephthalate (PET) and polyethylene-2,6-naphthalate (PEN), and polyamide resins such as nylon 6, nylon 66, nylon 12, and copolymer nylon. As the base film 113a, unstretched or stretched films made from these thermoplastic resins are preferred. In particular, polyester resins are preferred because they have excellent dimensional stability and are less likely to crack in the vapor deposition film. The base film 113a may be made of one thermoplastic resin film, or may be made by laminating two or more thermoplastic resin films directly or with a solventless adhesive layer that does not contain an organic solvent. In this case, neither an adhesive containing an organic solvent nor an anchor coating agent is contained between the thermoplastic resin films.

[0063] The second inorganic barrier layer 113c can have a similar structure to the first inorganic barrier layer 113b. Since the second inorganic barrier layer 113c exists between the base film 113a and the sealant film 111, even if the base film 113a contains an ultraviolet absorbing component, the ultraviolet absorbing component will not migrate to the sealant film 111 and will not be dissolved into the test liquid 2.

[0064] Second Modification of the First Embodiment A second modified example of the first embodiment of the laminate film of the present invention will be described with reference to Fig. 1C. The laminate film 101C of the second modified example includes a sealant film 111 and a barrier film 113. The barrier film 113 of the second modified example has a first inorganic barrier layer 113b on the surface of the base film 113a opposite to the surface facing the sealant film 111, and a second inorganic barrier layer 113c on the surface facing the sealant film 111.

[0065] (Sealant Film 111) The sealant film 111 is similar to the basic sealant film 111 described above. (Barrier Film 113) The barrier film 113 is a film with excellent gas barrier properties such as water vapor barrier properties, and the laminated film 101A of this embodiment including the barrier film 113 also has excellent gas barrier properties. By filling the bag made of the laminated film 101A with the test liquid 2, evaporation of water in the test liquid 2 during storage of the test liquid product 1 is suppressed, and the test liquid product 1 can be stably stored for a long period of time without reducing the amount of the test liquid 2. The base film 113a of the barrier film 113 is the same as the base film 113a of the first modified example described above. The first inorganic barrier layer 113b is the same as the first inorganic barrier layer 113b of the basic form described above. The second inorganic barrier layer 113c is the same as the second inorganic barrier layer 113c of the first modified example described above.

[0066] Furthermore, the laminated film 101C of the second modified example exhibits superior gas barrier performance due to the barrier film 113 including the first inorganic barrier layer 113b and the second inorganic barrier layer 113c.

[0067] Second embodiment <<Basic form of the second embodiment>> A second embodiment of the laminated film of the present invention will be described with reference to FIG. 2A. In order to distinguish from the modified examples described later, the embodiment shown in FIG. 2A may be referred to as the "basic form". First, the laminated film 201A of this embodiment includes a sealant film 111, a barrier film 113, and a cover film 114. The barrier film 113 of this basic form has a first inorganic barrier layer 113b on the side opposite to the side of the base film 113a facing the sealant film 111. In addition, in the laminated film 201A of this embodiment, the sealant film 111 and the barrier film 113 are laminated directly or via a solventless adhesive layer that does not contain an organic solvent. In other words, neither an adhesive containing an organic solvent nor an anchor coating agent is included between the sealant film 111 and the barrier film 113.

[0068] (Sealant Film 111) This is similar to the basic sealant film 111 of the first embodiment of the present invention described above. (Barrier Film 113) This is the same as the basic barrier film 113 of the first embodiment of the present invention described above. (Cover Film 114)

[0069] The cover film 114 of this embodiment protects the barrier film 113 described above. The cover film 114 is a film made of a thermoplastic resin. The thermoplastic resin used for the cover film 114 is preferably a polyamide resin or a polyester resin in terms of abrasion resistance, film strength, puncture resistance, transparency, and the like. The polyamide resin is preferably nylon, such as nylon 6, nylon 66, nylon 11, nylon 12, MXD nylon, and copolymer nylon. The polyester resin is preferably aromatic polyester resin, such as polyethylene terephthalate (PET) and polyethylene-2,6-naphthalate (PEN). The cover film 114 is preferably an unstretched or stretched film made of a polyamide resin or a polyester resin, more preferably a nylon film, and even more preferably a biaxially stretched nylon film (ONY) because of its excellent film strength. The thickness of the cover film 114 is preferably 7 to 100 μm.

[0070] Furthermore, in the laminate film 201A of this embodiment, the first inorganic barrier layer 113b is present between the cover film 114 and the base film 113a, so even if the cover film 114 contains an ultraviolet absorbing component, it will not migrate to the base film 113a or the sealant film 111, and the ultraviolet absorbing component will not dissolve into the test liquid 2.

[0071] First Modification of the Second Embodiment

[0072] A first modified example of the second embodiment of the laminated film of the present invention will be described with reference to Fig. 2B. The laminated film 201B of this embodiment includes a sealant film 111, a barrier film 113, and a cover film 114. The barrier film 113 of the first modified example has a second inorganic barrier layer 113c on the surface of the base film 113a facing the sealant film 111.

[0073] (Sealant Film 111) This is similar to the basic sealant film 111 of the first embodiment of the present invention described above. (Barrier Film 113) This is similar to the barrier film 113 of the first modified example of the first embodiment of the present invention described above. (Cover Film 114) This is the same as the basic cover film 114 of the second embodiment of the present invention described above.

[0074] Second Modification of the Second Embodiment A second modified example of the second embodiment of the laminated film of the present invention will be described with reference to Fig. 2C. The laminated film 201C of this embodiment includes a sealant film 111, a barrier film 113, and a cover film 114. The barrier film 113 of the second modified example has a first inorganic barrier layer 113b on the surface of the base film 113a opposite to the surface facing the sealant film 111, and a second inorganic barrier layer 113c on the surface facing the sealant film 111.

[0075] (Sealant Film 111) This is similar to the basic sealant film 111 of the first embodiment of the present invention described above. (Barrier Film 113) This is similar to the barrier film 113 of the second modified example of the first embodiment of the present invention described above. (Cover Film 114) This is the same as the basic cover film 114 of the second embodiment of the present invention described above.

[0076] Furthermore, in the laminate film 201C of the second modified example, the barrier film 113 includes the first inorganic barrier layer 113b and the second inorganic barrier layer 113c, and thus exhibits superior gas barrier performance.

[0077] Third embodiment <<Basic form of the third embodiment>> A third embodiment of the laminated film of the present invention will be described with reference to FIG. 3A. In order to distinguish from the modified examples described later, the embodiment shown in FIG. 3A may be referred to as the "basic form". The laminated film 301A of this embodiment includes a sealant film 111, a plastic film 112, and a barrier film 113. The barrier film 113 of this basic form has a first inorganic barrier layer 113b on the side opposite to the side of the base film 113a facing the sealant film 111. In the laminated film 301A of this embodiment, the sealant film 111 and the plastic film 112, and the plastic film 112 and the barrier film 113 are laminated directly or via a solventless adhesive layer that does not contain an organic solvent. In other words, neither an adhesive containing an organic solvent nor an anchor coating agent is contained between the sealant film 111 and the plastic film 112, and between the plastic film 112 and the barrier film 113.

[0078] (Sealant Film 111) This is similar to the basic sealant film 111 of the first embodiment of the present invention described above.

[0079] (Plastic Film 112) If a plastic film is provided between the sealant film 111 and the barrier film 113, the film strength and puncture strength of the laminated film 101 can be increased. The plastic film 112 is a film made of a thermoplastic resin. Examples of the thermoplastic resin used for the plastic film 112 include the above-mentioned additive-free polyolefin, polyamide resin, polyester resin, and ethylene-based polymer. Examples of the polyamide resin include nylon 6, nylon 66, nylon 11, nylon 12, MXD nylon, and copolymer nylon. As the nylon film, it is preferable to use a biaxially oriented nylon film (ONY) because of its excellent film strength. As the polyester resin, polyethylene terephthalate (PET) is preferable. Examples of the ethylene-based polymer include an ethylene-vinyl alcohol copolymer, an ethylene-(meth)acrylic acid copolymer, an ethylene-(meth)acrylic acid ester copolymer, and an ethylene-vinyl acetate copolymer. As the thermoplastic resin, additive-free polyolefin is preferable because it does not contain an ultraviolet absorbing component. The thickness of the plastic film 112 is not particularly limited, but is preferably 7 to 100 μm. The sealant film 111 and the plastic film 112 are laminated together directly or via a solventless adhesive layer that does not contain an organic solvent, without using any adhesive or anchor coating agent that contains an organic solvent. The plastic film 112 may be made of a single thermoplastic resin film, or may be made by laminating two or more thermoplastic resin films together directly or via a solventless adhesive layer that does not contain an organic solvent. In this case, neither an adhesive nor an anchor coating agent that contains an organic solvent is used between the thermoplastic resin films.

[0080] (Barrier Film 113) This is the same as the basic barrier film 113 of the first embodiment of the present invention described above.

[0081] First Modification of the Third Embodiment A first modified example of the third embodiment of the laminate film of the present invention will be described with reference to Fig. 3B. The laminate film 301B of this embodiment includes a sealant film 111, a plastic film 112, and a barrier film 113. The barrier film 113 of the first modified example has a second inorganic barrier layer 113c on the surface of the base film 113a facing the sealant film 111.

[0082] (Sealant Film 111) This is similar to the basic sealant film 111 of the first embodiment of the present invention described above. (Plastic Film 112) This is the same as the basic plastic film 112 of the third embodiment of the present invention described above. (Barrier Film 113) This is similar to the barrier film 113 of the first modified example of the first embodiment of the present invention described above.

[0083] Second Modification of the Third Embodiment A second modified example of the third embodiment of the laminate film of the present invention will be described with reference to Fig. 3C. The laminate film 301C of this embodiment includes a sealant film 111, a plastic film 112, and a barrier film 113. The barrier film 113 of the second modified example has a first inorganic barrier layer 113b on the surface of the base film 113a opposite to the surface facing the sealant film 111, and a second inorganic barrier layer 113c on the surface facing the sealant film 111.

[0084] (Sealant Film 111) This is similar to the basic sealant film 111 of the first embodiment of the present invention described above. (Plastic Film 112) This is the same as the basic plastic film 112 of the third embodiment of the present invention described above. (Barrier Film 113) This is similar to the barrier film 113 of the second modified example of the first embodiment of the present invention described above.

[0085] Fourth embodiment <<Basic form of the fourth embodiment>> A fourth embodiment of the laminated film of the present invention will be described with reference to FIG. 4A. In order to distinguish from the modified examples described later, the embodiment shown in FIG. 4A may be referred to as the "basic form". The laminated film 401A of this embodiment includes a sealant film 111, a plastic film 112, a barrier film 113, and a cover film 114. The barrier film 113 of this basic form has a first inorganic barrier layer 113b on the side opposite to the side of the base film 113a facing the sealant film 111. In the laminated film 401A of this embodiment, the sealant film 111 and the plastic film 112, and the plastic film 112 and the barrier film 113 are laminated directly or via a solventless adhesive layer that does not contain an organic solvent. In other words, neither an adhesive containing an organic solvent nor an anchor coating agent is contained between the sealant film 111 and the plastic film 112, and between the plastic film 112 and the barrier film 113.

[0086] (Sealant Film 111) This is similar to the basic sealant film 111 of the first embodiment of the present invention described above. (Plastic Film 112) This is the same as the basic plastic film 112 of the third embodiment of the present invention described above. (Barrier Film 113) This is the same as the basic barrier film 113 of the third embodiment of the present invention described above. (Cover Film 114) This is the same as the basic cover film 114 of the second embodiment of the present invention described above.

[0087] First Modification of the Fourth Embodiment A first modified example of the fourth embodiment of the laminated film of the present invention will be described with reference to Fig. 4B. The laminated film 401B of this embodiment includes a sealant film 111, a plastic film 112, a barrier film 113, and a cover film 114. The barrier film 113 of the first modified example has a second inorganic barrier layer 113c on the surface of the base film 113a facing the sealant film 111.

[0088] (Sealant Film 111) This is similar to the basic sealant film 111 of the first embodiment of the present invention described above. (Plastic Film 112) This is the same as the basic plastic film 112 of the third embodiment of the present invention described above. (Barrier Film 113) This is the same as the barrier film 113 of the first modified example of the third embodiment of the present invention described above. (Cover Film 114) This is the same as the cover film 114 of the first modified example of the second embodiment of the present invention described above.

[0089] Second Modification of the Fourth Embodiment A second modified example of the fourth embodiment of the laminated film of the present invention will be described with reference to Fig. 4C. The laminated film 401C of this embodiment includes a sealant film 111, a plastic film 112, a barrier film 113, and a cover film 114. The barrier film 113 of the second modified example has a first inorganic barrier layer 113b on the surface of the base film 113a opposite to the surface facing the sealant film 111, and a second inorganic barrier layer 113c on the surface facing the sealant film 111.

[0090] (Sealant Film 111) This is similar to the basic sealant film 111 of the third embodiment of the present invention described above. (Plastic Film 112) This is the same as the basic plastic film 112 of the third embodiment of the present invention described above. (Barrier Film 113) This is similar to the barrier film 113 of the second modified example of the third embodiment of the present invention described above. (Cover Film 114) This is similar to the cover film 114 of the second modified example of the second embodiment of the present invention described above.

[0091] Examples of preferred laminate films include four-layer laminate films such as ONY / silicon oxide vapor-deposited PET film / additive-free LDPE / additive-free LDPE, ONY / silicon oxide vapor-deposited PET film / additive-free LDPE / additive-free LLDPE, and ONY / silicon oxide vapor-deposited PET film / EMAA (ethylene-acrylic acid copolymer) / additive-free LLDPE. <Manufacturing method>

[0092] The laminated films 101A to 401C of the first to fourth embodiments of the present invention can be manufactured by laminating the sealant film 111 and the barrier film 113, the sealant film 111 and the barrier film 113 and the cover film 114, the sealant film 111 and the plastic film 112 and the barrier film 113, and the sealant film 111 and the plastic film 112 and the barrier film 113 and the cover film 114 to a predetermined layer structure. The lamination method of the cover film 114 and the barrier film 113 is not particularly limited, and known methods such as a dry lamination method using an adhesive and an extrusion lamination method using a thermal adhesive resin or the like can be used. In addition, as the adhesive used in the dry lamination method, a polyurethane adhesive, a polyester adhesive, an acrylic adhesive, or the like is preferable. Among the dry lamination methods, the dry lamination method using a polyurethane adhesive is preferable because it is less likely to cause elution problems and has excellent adhesive strength. In particular, polyurethane adhesives using a polyester-based polyol as the polyol component (hereinafter, referred to as polyester-based polyurethane adhesives) are preferred because they have excellent acid resistance and cause less components to leach out from the laminated film.

[0093] Moreover, the lamination method of the sealant film 111 and the barrier film 113, the lamination method of the barrier film 113 and the plastic film 112, and the lamination method of the plastic film 112 and the sealant film 111 do not use any adhesive containing an organic solvent or an AC agent (anchor coating agent), and as a direct lamination method, for example, an extrusion lamination method or a thermal lamination method using a thermal adhesive resin or the like without using an AC agent can be used. As a method of adhesion using a solventless adhesive layer that does not contain an organic solvent, a non-solvent lamination method or a wet lamination method using an aliphatic ester adhesive, an aromatic ether adhesive, or other water-soluble or emulsion type adhesive that does not use an organic solvent can be used.

[0094] When the above films are to be bonded together, it is preferable to subject the films to a surface treatment, such as a corona discharge treatment, a plasma treatment, or an electron beam or radiation treatment.

[0095] A container suitable for the test liquid product 1 of the present invention includes a bag-shaped container body 3 for accommodating the test liquid 2, and the container body 3 is composed of the laminated films 101A to 401C described above.

[0096] Next, the present invention will be described in more detail with reference to examples. However, the present invention is not limited to the examples described below, and various modifications are possible without departing from the gist of the invention. (Dissolution test) [Preparation of test solution]

[0097] The following test liquid 2 was prepared. Test solution A: Japanese Pharmacopoeia purified water (Kyoei Pharmaceutical Co., Ltd.) Test solution B: Disintegration test solution 1, pH 1.2 / Dissolution test solution 1, pH 1.2 (Kanto Chemical Co., Ltd.) EXAMPLES

[0098] <ONY 15 μm / Dry / Vapor-deposited PET 12 μm / Extruded LDPE (Additive-free) 20 μm / LDPE (Additive-free) 100 μm / Test Liquids A, B> ONY (manufactured by Unitika Ltd., emblem ON, thickness 15 μm), and an inorganic oxide vapor-deposited film, Tech Barrier HX (manufactured by Mitsubishi Chemical Corporation, thickness 12 μm) were dry laminated using a polyester-based polyurethane adhesive (manufactured by Toyo Morton Co., Ltd., Tomoflex TM-250). Further, without using an AC agent, an additive-free LDPE film (manufactured by Tamapoly Co., Ltd., SK615P, 100 μm) was extrusion laminated using LDPE (manufactured by Tosoh Corporation, Petrothene DLZ10A, 20 μm) by the extrusion lamination method to obtain a laminated film 201B. Using this laminated film, a container in the form shown in Fig. 5 was produced, filled with Test Liquids A and B, and Test Liquid Product 1 was manufactured. Then, the manufactured Test Liquid Product 1 was evaluated by the evaluation method described below.

Example

[0099] <ONY 15 μm / Dry / Vapor-deposited PET 12 μm / Extruded LDPE (Additive-free) 20 μm / LLDPE (Additive-free) 100 μm / Test Liquids A, B> ONY (manufactured by Unitika Ltd., emblem ON, thickness 15 μm), and an inorganic oxide vapor-deposited film, Tech Barrier HX (manufactured by Mitsubishi Chemical Corporation, thickness 12 μm) were dry laminated using a polyester-based polyurethane adhesive (manufactured by Toyo Morton Co., Ltd., Tomoflex TM-250). Further, without using an AC agent, an additive-free LLDPE film (manufactured by Tamapoly Co., Ltd., SF625P, 100 μm) was extrusion laminated using LDPE (manufactured by Tosoh Corporation, Petrothene DLZ10A, 20 μm) by the extrusion lamination method to obtain a laminated film 201B. Using this laminated film, a container in the form shown in Fig. 5 was produced, filled with Test Liquids A and B, and Test Liquid Product 1 was manufactured. Then, the manufactured Test Liquid Product 1 was evaluated by the evaluation method described below.

Example

[0100] <ONY 25 μm / Dry / Transparent VMPET 12 μm / Extruded EMAA 20 μm / LLDPE 100 μm (Additive-free) / Test Liquids A, B> ONY (manufactured by Unitika, emblem ON, thickness 15 μm) and transparent barrier film VMPET Clarista CI (manufactured by Kuraray, thickness 12 μm) were laminated by the dry lamination method using a polyester-based polyurethane adhesive (manufactured by Toyo Morton, Tomoflex TM-250). Further, without using an AC agent, EMAA (ethylene-methacrylic acid copolymer, manufactured by Mitsui Dow Polychemicals, Nuclel N1108C, 20 μm) was used to laminate an additive-free LLDPE film (manufactured by Tamapoly, SK615P, 100 μm) by the extrusion lamination method to obtain a laminated film 201B. Using this laminated film, a container in the form shown in Fig. 5 was produced, and test liquids A and B were filled to manufacture test liquid product 1. Then, the manufactured test liquid product 1 was evaluated by the evaluation method described later.

[0101] [Comparative Example 1] <ONY 15 μm / Dry / Vapor-deposited PET 12 μm / AC / Extruded LLDPE 100 μm / Test Liquids A, B> ONY (manufactured by Unitika, emblem ON, thickness 15 μm) and inorganic oxide vapor-deposited film Tech Barrier HX (manufactured by Mitsubishi Chemical, thickness 12 μm) were laminated by the dry lamination method using a polyester-based polyurethane adhesive (manufactured by Toyo Morton, Tomoflex TM-250). Further, an extrusion layer of LLDPE (manufactured by Prime Polymer, Ultra Zex 100 μm) was formed using an AC agent for extrusion lamination (manufactured by Toyo Morton, EL-510) to obtain a laminated film. Using this laminated film, a container in the form shown in Fig. 5 was produced, and test liquids A and B were filled to manufacture test liquid product 1. Then, the manufactured test liquid product 1 was evaluated by the evaluation method described later.

[0102] [Comparative Example 2] <PET 16 μm / Dry / ONY 25 μm / Dry / Vapor-deposited PET 12 μm / AC / Extruded LLDPE 100 μm / Test Liquids A, B> A biaxially oriented PET film (manufactured by Unitika Ltd., Emblet PET, thickness 16 μm), ONY (manufactured by Unitika Ltd., Emblem ON, thickness 25 μm), and an inorganic oxide vapor-deposited film Tech Barrier HX (manufactured by Mitsubishi Chemical Corporation, thickness 12 μm) were laminated by the dry lamination method using a polyester-based polyurethane adhesive (manufactured by Toyo Morton Co., Ltd., Tomoflex TM-250). Further, an LLDPE (manufactured by Prime Polymer Co., Ltd., Ultra Zex 100 μm) extrusion layer was formed using an AC agent for extrusion lamination (manufactured by Toyo Morton Co., Ltd., EL-510) to obtain a laminated film. Using this laminated film, a container in the form shown in Fig. 5 was produced, and test liquids A and B were filled to produce test liquid product 1. Then, the manufactured test liquid product 1 was evaluated by the evaluation method described later.

[0103] [Comparative Example 3] <ONY 15 μm / AC / extrusion / LLDPE 70 μm / test liquids A and B> A commercially available stand-up bag (manufactured by Coupack Co., Ltd., TP-S0350) with the above configuration was filled with test liquids A and B to produce test liquid product 1. Then, it was evaluated by the evaluation method described later.

[0104] [Comparative Example 4] <PET 12 μm / dry / vapor-deposited PET 12 μm / dry / ONY 15 μm / dry / LLDPE 130 μm / test liquids A and B> A commercially available stand-up bag with a two-piece cap (manufactured by Coupack Co., Ltd., DP16-TW0400) configured as above was filled with test liquids A and B to produce test liquid product 1. Then, it was evaluated by the evaluation method described later.

[0105] [Comparative Example 5] <Vapor-deposited PET 12 μm / dry / PET 12 μm / dry / ONY 15 μm / dry / LLDPE 130 μm / test liquids A and B> An inorganic oxide deposition film (Techbarrier HX, manufactured by Mitsubishi Chemical Corporation, thickness 12 μm), a biaxially oriented PET film (Unitika Ltd., Emblet PET, thickness 12 μm), ONY (Unitika Ltd., Emblem ON, thickness 15 μm), and an LLDPE film (Tamapoly Corporation, UB106, thickness 130 μm) were laminated by a dry lamination method using a polyester-based polyurethane adhesive (Tomoflex TM-250, manufactured by Toyo-Morton Co., Ltd.) to obtain a laminated film. A container having a shape as shown in FIG. 5 was made using this laminated film, and test liquids A and B were filled therein to produce test liquid product 1. The produced test liquid product 1 was then evaluated by the evaluation method described below.

[0106] [Evaluation method] The test liquid products 1 obtained in Examples 1 to 3 and Comparative Examples 1 to 5 were evaluated as follows.

[0107] (Amount of UV-absorbing elution due to storage) The test liquid product 1 of each example was stored for 60 days at 40° C. Thereafter, test liquids A and B were extracted from each test liquid product 1, and the absorbance at wavelengths of 220 nm and 250 nm was measured using a UV absorption measuring device (Hitachi spectrophotometer, U-3000) to be used as an index of the amount of eluted ultraviolet-absorbing eluate.

[0108] The results are shown in the "Absorbance" column in Tables 1 and 2. As a result, for Examples 1, 2, and 3 in which additive-free polyolefin was used for the sealant film 111 constituting the test liquid product 1, and the sealant film and barrier film were directly laminated without using either an AC agent or an adhesive, no ultraviolet absorption was observed in test liquids A and B after storage.

[0109] (Weight loss during storage) The test liquid product 1 of each example was stored at 40° C. for 60 days. The mass of each test liquid product 1 was measured before and after storage, and the weight loss per bag per day was calculated. The results are shown in the “Weight Loss” column in Tables 1 and 2. [Table 1] [Table 2]

[0110] [Results explanation] (Amount of UV-absorbing elution due to storage) In the test liquid products 1 of Examples 1 to 3, in which additive-free polyolefin was used for the sealant film 111 that constitutes the test liquid product 1 and the sealant film and barrier film were directly laminated without using either an AC agent or an adhesive, almost no ultraviolet absorption was observed in the test liquid 2 after storage.

[0111] (Weight loss during storage) The mass loss of the test liquid products 1 of Examples 1 to 3 and Comparative Examples 1, 2, 4 and 5, which were constructed using a laminated film including a barrier film (evaporated PET 12μ) on which an inorganic oxide was vapor-deposited, was extremely small, and sufficient water vapor permeation barrier properties were observed. (Degassing test) EXAMPLES

[0112] 70 mL of concentrated hydrochloric acid (Kanto Chemical Co., Ltd., special grade reagent) and 20.0 g of sodium chloride (Wako Pure Chemical Industries, Ltd., special grade reagent) were accurately measured and dissolved in Japanese Pharmacopoeia purified water (Kyoei Pharmaceutical Co., Ltd.) to make the total volume exactly 10 L, and test liquid 2 was obtained. Next, test liquid 2 was degassed using a degassing module using a hollow fiber membrane. The degassing degree of this test liquid 2 was 3.2 mg / L in terms of dissolved oxygen concentration. In addition, a laminated bag made of a film in which a nylon film (base film 113a), an aluminum foil (second inorganic barrier layer 113c), and an additive-free low-density polyethylene film (sealant film 111) were laminated was prepared. Then, 900 mL of the obtained test liquid 2 was accurately dispensed into a 900 mL volumetric flask and filled from the upper opening of the laminated bag. After that, the air in the container was removed using a degassing sealer, and the upper opening of the laminated bag was heat-sealed to close it, and test liquid product 1 was obtained. The remaining test liquid 2 was subjected to the same procedure (fractionation, filling into laminated bags, and sealing) to obtain 11 test liquid products 1 each containing 900 mL of the first dissolution test liquid accurately. The head space 30 of the test liquid product 1 was 1% or less of the volume of the test liquid 2 (900 mL). EXAMPLES

[0113] 17.0 g of potassium dihydrogen phosphate (special grade reagent, manufactured by Kanto Chemical) and 17.75 g of disodium dihydrogen phosphate (special grade reagent, manufactured by Kanto Chemical) were accurately measured and dissolved in Japanese Pharmacopoeia purified water (manufactured by Kyoei Pharmaceutical Co., Ltd.) to make the total volume exactly 10 L, and test liquid 2 was obtained. Next, test liquid 2 was degassed using a degassing module using a hollow fiber membrane. The degree of degassing of this test liquid 2 was equivalent to that of [Example 1]. In addition, a laminated bag made of a film in which a polyethylene terephthalate film (base film 113a), an aluminum foil, a nylon film (second inorganic barrier layer 113c), and an additive-free polypropylene film (sealant film 111) were laminated in this order was prepared. Then, 900 mL of the obtained test liquid 2 was accurately dispensed into a 900 mL volumetric flask and filled from the upper opening of the laminated bag. Thereafter, the air in the container was removed using a degassing sealer, and the upper opening of the laminated bag was heat-sealed to close it, and test liquid product 1 was obtained. The remaining test liquid 2 was subjected to the same procedure (fractionation, filling into laminated bags, sealing) to obtain 11 test liquid products 1 each containing 900 mL of the second dissolution test liquid (diluted phosphate buffer solution at pH 6.8). The head space 30 of the test liquid product 1 was 1% or less of the volume of the test liquid 2 (900 mL). EXAMPLES

[0114] 71.0 g of anhydrous disodium hydrogen phosphate (manufactured by Wako Pure Chemical Industries, special grade reagent) was dissolved in Japanese Pharmacopoeia purified water (manufactured by Kyoei Pharmaceutical Co., Ltd.) to make 10 L. To this liquid, 53 g of citric acid monohydrate (manufactured by Junsei Pharmaceutical, special grade reagent) was dissolved in Japanese Pharmacopoeia purified water (manufactured by Kyoei Pharmaceutical Co., Ltd.) to make 10 L, and the pH was adjusted to 8.0 to obtain test liquid 2. Next, test liquid 2 was degassed using a degassing module using a hollow fiber membrane. The degassing degree of this test liquid 2 was equivalent to that of [Example 1]. In addition, a laminated bag was prepared, which was made of a film in which a polyethylene terephthalate film (base film 113a), an aluminum foil, a nylon film (second inorganic barrier layer 113c), and an additive-free polypropylene film (sealant film 111) were laminated in this order. Then, 900 mL of the obtained test liquid 2 was accurately dispensed into a 900 mL volumetric flask and filled from the upper opening of the above laminated bag. After that, the air was removed from the container using a vacuum sealer, and the top opening of the laminated bag was heat sealed to obtain test liquid product 1. The remaining test liquid 2 was subjected to the same procedure (dispensing, filling into laminated bags, sealing) to obtain 12 test liquid products 1 each containing 900 mL of pH 8.0 dibasic sodium phosphate citrate buffer solution. The headspace 30 of test liquid product 1 was less than 1% of the volume of test liquid 2 (900 mL).

[0115] When the dissolved oxygen concentration of the test liquid 2 in each of Examples 4 to 6 was measured after being left for 10 days, no significant change was observed, and the dissolved oxygen concentration was maintained at 6 mg / L or less.

[0116] As described above, in the container body 3 suitable for the test liquid product 1 according to the present invention, the sealant film 111 on the content side of the laminated films 101A to 401C constituting the container body 3 is made of additive-free polyolefin, and at least the sealant film 111 to the barrier film 113 are laminated directly or via a solvent-free adhesive layer that does not contain organic solvents without using any adhesive or anchor coating agent containing organic solvents, so that components such as organic solvents do not dissolve into the content side. This makes it possible to prevent adverse effects on the content due to these dissolutions. In particular, in the test liquid product 1 in which the content is the test liquid 2, components having ultraviolet absorption do not dissolve into the test liquid 2, and accurate test results with few errors can be obtained.

[0117] In addition, the container body 3 suitable for the test liquid product 1 of the present invention has laminate films 101A-401C constituting the container body 3, which include a barrier film 113 (hereinafter sometimes simply referred to as "barrier film 113") having inorganic barrier layers 113b, 113c, thereby preventing deterioration of the test liquid 2 during storage of the test liquid product 1 for test liquids 2 with a wide range of pH values.

[0118] That is, the laminated films 101A to 401C are provided with excellent gas barrier properties by the barrier film 113. Therefore, by storing the test liquid 2 in the container body 3 composed of the laminated films 101A to 401C, evaporation of the water contained in the test liquid 2 can be suppressed. Therefore, evaporation of water during storage of the test liquid product 1, and the associated decrease in the amount of the test liquid 2 and change in pH can be suppressed. As an example of this specific effect, the test liquid 2 used in the dissolution test needs to be used accurately within a range of ±1% of the specified volume, but the test liquid product 1 of the present invention can maintain the test liquid volume within a range of 900mL ±1% even after 180 days when filled with 900mL of the test liquid 2 and stored at a temperature of 40°C or less.

[0119] In addition, by using the barrier film 113, elution from the container body 3 into the test liquid 2 is less likely to occur than when other known gas barrier films are used. Conventionally, in applications requiring water vapor barrier properties, coated films in which an organic and / or inorganic barrier coating agent (e.g., polyvinylidene chloride, ethylene-vinyl alcohol copolymer, crosslinked product of modified or unmodified polyvinyl alcohol and unsaturated carboxylate, etc.) is coated on a base film have been widely used as gas barrier films. However, according to the study by the present inventors, when these gas barrier films are used, there is a problem that eluted substances are mixed into the test liquid 2. For example, in the case of a coated film, there is a problem that organic or inorganic coating agent components are eluted from the formed coating layer into the test liquid 2. And, in particular, elution of organic components affects the measured value of the active ingredient in the elution test, hindering the quantification of the active ingredient. In this regard, the container body 3 suitable for the test liquid product 1 of the present invention uses laminated films 101A-401C equipped with a barrier film 113 in the container body 3, so that, as mentioned above, there is little leaching from the container body 3 into the test liquid 2, and accurate test results with little error can be obtained.

[0120] Furthermore, by using the test liquid product 1 of the present invention, the workload of the tester in the dissolution test or disintegration test can be greatly reduced. For example, in the test liquid product 1 of the present invention, the test liquid 2 used in the dissolution test or disintegration test is filled directly into the container body 3, and the decrease or denaturation during storage is also suppressed, so the tester can start the dissolution test or disintegration test simply by opening the container body 3 and transferring a part or all of the content liquid to a test container. Therefore, some or all of the pre-test work required for the test, such as weighing the reagents and water required for preparing the test liquid 2, stirring and dissolving, work in a draft chamber required for using strong acids such as concentrated hydrochloric acid when preparing a strongly acidic test liquid 2, measuring and adjusting the pH, and accurately taking a specified amount of test liquid 2 (for example, 900 mL) from a large amount of test liquid 2, which have been conventionally performed by the tester, can be omitted.

[0121] Furthermore, even if the test liquid 2 requires degassing, the test liquid product 1 according to the present invention is filled with the test liquid 2 that has been degassed in advance, so the tester can start the dissolution test simply by opening the container body 3, transferring the test liquid 2 directly into the test container, and heating it to a specified temperature (37°C). This configuration not only eliminates the need for the preparatory work required for the above-mentioned test that was previously performed by the tester, but also eliminates the need for the troublesome degassing work (heating, reducing pressure, filtering, etc. to degas the test liquid).

[0122] Furthermore, for example, when the entire content liquid is transferred, that is, when the filling amount of the test liquid 2 is within ±1% of the volume specified as the amount of the test liquid 2 used in one dissolution test or disintegration test, all of the above preparatory steps can be omitted. Furthermore, in this case, since the entire amount of the filled test liquid 2 is used up in one go, contamination and proliferation of microorganisms are unlikely to occur.

[0123] In addition, when transferring a part of the test liquid 2, the work of dispensing is necessary, but other preparatory work can be omitted. Regarding the work of dispensing, the transferred amount of liquid can be accurately calculated by simply measuring the weight of the test liquid product 1 before and after the transfer.

[0124] In addition, since dissolution tests and disintegration tests are performed at 37°C, generally, a specified amount of test liquid 2 is placed in a test container and then heated to 37°C. In contrast, if the test liquid product 1 of the present invention is heated to 37°C in advance together with the container body 3 in a thermostatic bath or the like, the test can be started immediately after the content liquid is transferred to the test container. This saves time before the test can be started, and the efficiency of the test can be improved. In particular, the test liquid product 1 filled with the test liquid 2 that has been degassed in advance can be heated to the test temperature of 37°C while maintaining the degassed state, so there is no need to worry about reabsorption of air during heating, and the time before the test can be saved, greatly improving the efficiency of the test. In this way, the test liquid product 1 of the present invention has epoch-making convenience.

[0125] In addition, the container body 3 suitable for the test liquid product 1 according to the present invention has the advantage that the container body 3 can be folded flat after the contents (test liquid 2) are removed, so there is little waste after the contents are removed. That is, since the container body 3 suitable for the present invention is a bag-shaped body made of a laminated film, the volume of the container body 3 is significantly reduced after the contents are removed. Therefore, compared to the use of a bottle-shaped or plastic tank-shaped container, the waste (empty container after use) is reduced in both mass and volume. In addition, when the container body 3 is self-supporting, it does not take up as much storage space or space during testing as when a non-self-supporting container is used, and the tester's work space is increased, improving workability.

[0126] The test liquid product 1 of the present invention allows the test liquid 2 used in the dissolution test or disintegration test to be stored without deterioration, and makes quality control easy. In particular, when the container body 3 suitable for the present invention is used, there is no dissolution of ultraviolet absorbing components into the test liquid 2, and there is no adverse effect on the results of the dissolution test or disintegration test, so more accurate test results can be obtained.

[0127] The test liquid product 1 of the present invention may be a dissolution test liquid product filled with the test liquid 2 used in the dissolution test (hereinafter also referred to as the dissolution test liquid) as described above, or a dissolution test liquid product filled with the test liquid 2 used in the disintegration test (hereinafter also referred to as the disintegration test liquid). However, since there are more types of dissolution test liquids than disintegration test liquids and the amount of liquid used in one test is strictly regulated, the test liquid product 1 of the present invention is more effective in reducing the burden on the tester by the present invention, as described above.

[0128] Furthermore, the container, container body 3, test liquid product 1, laminated films 101A to 401C, etc. shown in this example are merely examples and are not limited to the above examples, and the present invention can be modified and implemented within the scope that does not deviate from the gist of the present invention. [Explanation of symbols]

[0129] 1 Test liquid products 2. Test solution 3 Container body 30 Headspace 111 Sealant film 112 Plastic Film 113 Barrier Film 113a Base film 113b, 113c Inorganic barrier layer 114 Cover Film 101A~401C Laminated Film

Claims

1. A test liquid used for dissolution testing or disintegration testing of solid dosage forms; A test liquid product having a container body filled with the test liquid, A test liquid product characterized in that the amount of air dissolved in the test liquid is 0 mg / L to 6 mg / L in terms of a dissolved oxygen concentration.

2. When the dissolved oxygen concentration of the test liquid is x and the volume ratio of the head space in the container body to the volume of the test liquid is y, y≦-0.0231x 3 +0.1867x 2 -0.6804x+2.3516 2. The test liquid product according to claim 1, wherein the test liquid product satisfies the above.

3. 3. The test liquid product according to claim 2, wherein the dissolved oxygen concentration of the test liquid is 0 mg / L to 4.5 mg / L, and the volume ratio of the head space in the container body to the amount of the test liquid is 0 vol.% to 1 vol.%.

4. 4. The test liquid product according to claim 1, wherein the filling volume of the test liquid is within a range of ±1% of the specified volume for one dissolution test.

5. A test liquid product described in any one of claims 1 to 4, characterized in that the container body comprises a sealant film made of an additive-free polyolefin and a barrier film having an inorganic barrier layer on one or both sides of a base film made of a thermoplastic resin, and is composed of a laminated film in which the sealant film and the barrier film are directly laminated together.

6. A test liquid product described in any one of claims 1 to 4, characterized in that the container body comprises, in this order, a sealant film made of an additive-free polyolefin, a plastic film made of a thermoplastic resin, and a barrier film having an inorganic barrier layer on one or both sides of a base film made of a thermoplastic resin, and is composed of a laminated film in which the sealant film and the plastic film are directly laminated together, and the plastic film and the barrier film are directly laminated together.

7. 5. A test liquid product according to any one of claims 1 to 4, characterized in that the container body comprises a sealant film made of an additive-free polyolefin and a barrier film having an inorganic barrier layer on one or both sides of a base film made of a thermoplastic resin, the sealant film and the barrier film being adhered to each other by a solvent-free adhesive layer that does not contain an organic solvent, comprising a laminated film.

8. 5. The test liquid product according to any one of claims 1 to 4, characterized in that the container body comprises, in this order, a sealant film made of an additive-free polyolefin, a plastic film made of a thermoplastic resin, and a barrier film having an inorganic barrier layer on one or both sides of a base film made of a thermoplastic resin, the sealant film and the plastic film being adhered to each other by a solvent-free adhesive layer that does not contain an organic solvent, and the plastic film and the barrier film being adhered to each other by a solvent-free adhesive layer that does not contain an organic solvent, forming a laminated film.

9. 9. The test liquid product according to claim 5, wherein the container body is made of a laminated film further having a cover film made of a thermoplastic resin on the barrier film side.

Citation Information

Patent Citations

  • Test liquid product

    JP2014070964A